Pengaruh Layanan Bimbingan Kelompok, Kemampuan Berinteraksi Sosial, Kontrol Diri dan Peningkatan Kualitas Kegiatan Belajar terhadap Motivasi Berprestasi dalam Belajar - Deliani Gea; Famahato Lase; Mondang Munthe; Hosianna Rodearni Damanik (Departement of Mathematics Education, 2024)
Motivation for achievement in learning can be increased with various guidance and counseling services with appropriate and appropriate techniques. The aim of the research is to reveal the influence of group guidance services (X1), social interaction skills (X2), self-control (X3), improving the quality of learning activities (X4) on achievement motivation in learning (Y), using the associative strategy quantitative method. The research location was students at SMP Negeri 1 Gunungsitoli, the research population was all class VIII students and the sample was drawn purposively as many as 32 people. The data collection instrument was a closed questionnaire which was distributed to a number of respondents. Data were analyzed using multiple linear regression analysis, to answer research questions according to the proposed hypothesis. The results of the research concluded that group guidance services, social interaction skills, self-control, improving the quality of learning activities, provide a very large influence and distribution on achievement motivation in learning. It is recommended that BK teachers use this service to increase achievement motivation in learning.